Alien Reptiles and Amphibians - Kraus, Fred (Springer, 2017)
The conservation threat posed by invasive alien species has become well-recognized over the past two decades, even as the problem continues to increase rapidly in scope. Research and management attention to this issue has, however, been taxonomically biased toward groups having large, obvious impacts, and the invasive potential of other organisms with subtle or cryptic impacts remains largely unassessed. Alien reptiles and amphibians, although providing a few of the better-known examples of severe invasion impacts, have never been scientifically assessed as a group for their potential invasiveness. This book examines the means by which alien reptiles and amphibians are transported by humans; surveys their ecological, evolutionary, economic, and health impacts; reviews the management responses taken against them; and summarizes the immediate research and management efforts needed to mitigate the threat posed by these organisms. It also provides a comprehensive database of herpetofaunal introductions worldwide and a bibliography of supporting literature. The purpose of the book is to summarize our current understanding of herpetofaunal invasiveness and stimulate additional management and research activities needed to reduce the impacts of these species.